Leak-before-break and plastic collapse strength evaluation of stainless steel piping with a part-through notch - Masato OGAWA (The Japan Society of Mechanical Engineers, 2020)
Nuclear power plants and chemical plants contain many piping, which degrades with age. As a result of a reduction in structural strength, guillotine breaking and rupturing can occur, leading to severe damage to plants. Piping is subjected to various types of tension and bending, but the influence of the load history on the integrity of piping containing a flaw is poorly understood. The goal of the present study was to develop an improved integrity assessment method for a stainless steel pipe with a part-through notch that takes into account the load history. This involved first determining the feasibility of the leak-before-break (LBB) concept for piping subjected to a combined load and then evaluating the stress at the crack penetration point and estimating the plastic collapse strength. An austenitic stainless steel pipe (SUS 304) with a length of 110 mm, a diameter of 32 mm, and a wall thickness of 3 mm was used as a specimen. A part-through notch with a notch angle of 90° was cut in the center of the specimen by wire electric discharge machining. Loading tests were carried out using statically indeterminate fracture mechanics testing equipment developed by ourselves. This allowed the loading history to be varied because the equipment is capable of applying arbitrary sequences of tension and bending. The LBB concept is considered to be applicable if the crack penetrates before reaching the maximum stress. The plastic collapse strength was then determined using the double elastic slope method. The LBB concept was found to be applicable. In addition, the stress at the crack penetration point was approximately equal to the maximum stress. The results of the present study indicated that the plastic collapse strength of a part-through notched specimen can be safely estimated using the theoretical plastic collapse strength of a through-wall notched pipe.